Проблемні питання безпеки дорожнього руху в Україні (повідомлення 2) = Topical issues of road-traffic safety in Ukraine (report 2) - Lebedeva, T. L. (Journal of Education, Health and Sport, 2015)
Lebedeva T. L. Проблемні питання безпеки дорожнього руху в Україні (повідомлення 2) = Topical issues of road-traffic safety in Ukraine (report 2). Journal of Education, Health and Sport. 2015;5(7):542-552. ISSN 2391-8306. DOI 10.5281/zenodo.28044 http://dx.doi.org/10.5281/zenodo.28044 https://pbn.nauka.gov.pl/works/607575 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%287%29%3A542-552 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.06.2015. Revised 15.07.2015. Accepted: 25.07.2015. ПРОБЛЕМНІ ПИТАННЯ БЕЗПЕКИ ДОРОЖНЬОГО РУХУ В УКРАЇНІ (ПОВІДОМЛЕННЯ 2) TOPICAL ISSUES OF ROAD-TRAFFIC SAFETY IN UKRAINE (report 2) Т. Л. Лєбєдєва T. L. Lebedeva ДП Український НДІ медицини транспорту МОЗ України, м. Одеса State Enterprise Ukrainian Research Institute for Medicine of Transport of the Ministry of Health Care of Ukraine, Odessa Abstract The influence of human’s psycho physiological peculiarities on the accident risk has been shown. The necessity of human’s psycho physiological peculiarities reporting at the planning crush rate measures decrease has been determined. The introduction of a compulsory psycho physiological examination for the accident participants with the aim of timely rehabilitative procedures conduction has been offered. Keywords: road traffic injuries, psychophysiology, post-traumatic stress. Резюме Показаний вплив психофізіологічних особливостей людини на ризик виникнення ДТП. Визначена необхідність врахування психофізіологічних особливостей людини при плануванні заходів щодо зниження дорожньо-транспортної аварійності. Запропоновано введення обов’язкового психофізіологічного обстеження учасників ДТП для своєчасного проведення реабілітаційних заходів. Ключові слова: дорожньо-транспортний травматизм, психофізіологія, посттравматичний стрес. Резюме ПРОБЛЕМНЫЕ ВОПРОСЫ БЕЗОПАСНОСТИ ДОРОЖНОГО ДВИЖЕНИЯ В УКРАИНЕ (СООБЩЕНИЕ 2). Показано влияние психофизиологических особенностей человека на риск возникновения ДТП. Определена необходимость учета психофизиологических особенностей человека при планировании мероприятий по снижению дорожно-транспортной аварийности. Предложено введение обязательного психофизиологического обследования участников ДТП для своевременного проведения реабилитационных мероприятий. Ключевые слова: дорожно-транспортный травматизм, психофизиология, посттравматический стресс.